2016
DOI: 10.1007/978-3-319-43624-1_18
|View full text |Cite
|
Sign up to set email alerts
|

Engineering and Directed Evolution of DNA Methyltransferases

Abstract: DNA methyltransferases (MTases) constitute an attractive target for protein engineering, thus opening the road to new ways of manipulating DNA in a unique and selective manner. Here, we review various aspects of MTase engineering, both methodological and conceptual, and also discuss future directions and challenges. Bacterial MTases that are part of restriction/modification (R/M) systems offer a convenient way for the selection of large gene libraries, both in vivo and in vitro. We review these selection metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…This method, originally devised for cloning DNA MTase genes ( 44 ) and complete restriction-modification systems ( 45 ), was later adopted for the selection of mutant MTases ( 46 , 47 ) notably those with altered specificity ( 8 , 37–39 , 41 , 48 ). Great advantages of the method are the physical linkage between the mutant genes and their encoded phenotypes manifested in the methylation patterns of the plasmid, and the powerful selection provided by restriction digestion ( 3 , 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…This method, originally devised for cloning DNA MTase genes ( 44 ) and complete restriction-modification systems ( 45 ), was later adopted for the selection of mutant MTases ( 46 , 47 ) notably those with altered specificity ( 8 , 37–39 , 41 , 48 ). Great advantages of the method are the physical linkage between the mutant genes and their encoded phenotypes manifested in the methylation patterns of the plasmid, and the powerful selection provided by restriction digestion ( 3 , 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…While the present study is rooted in a rational-design approach with molecular dynamics simulations guiding selection of mutagenesis candidates, our approach could be complemented by random mutagenesis studies or direct coupling analysis, which might further enhance the selectivity and/or activity profiles of CxMTases similar to those that have been used for other MTases. Directed evolution in particular has become one of the most powerful and widespread tools for improving desired protein function, especially when a selective pressure is applied . Indeed, the fact that the CxMTase activity can be observed in E. coli makes it viable that selection strategies could be employed to discover mutants that further alter either enzymatic efficiency or selectivity in favor of CxSAM over SAM.…”
Section: Discussionmentioning
confidence: 99%
“…Crystal structures and computational studies have provided us with knowledge about the reaction mechanisms and have identified critical active-site residues that influence the functional properties. This knowledge has enabled many research groups to use protein engineering methods to tailor active sites of enzymes for altered efficiency, substrate specificity or other desired features ( Norrgård et al , 2006 ; Laurino et al , 2016 ). However, currently used methods are limited in efficacy due to lack of solved protein structures and incomplete knowledge of the intricacies of enzyme catalysis.…”
Section: Introductionmentioning
confidence: 99%